2004
DOI: 10.22353/mjbs.2004.02.14
|View full text |Cite
|
Sign up to set email alerts
|

Illegal and Unsustainable Wildlife Hunting and Trade in Mongolia

Abstract: Recent reports and studies document dramatic declines in a wide variety of wildlife species in Mongolia. The prime driver in these declines appears to be illegal and unsustainable hunting, both for local trade and consumption and for the international market. While data on these declines are sparse, comparisons of survey reports since the 1980s present evidence that some species may have declined by up to 90% in recent years. We outline the situation for eight major species of wildlife in Mongolia (saiga antel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Our discussions with area residents suggested that during the late twentieth century, big game animals were regularly seen atop Tsengel Khairkhan, but have not been observed there in decades. Big game populations have declined dramatically across Mongolia during the last thirty years, primarily due to illegal poaching driven by international wildlife markets 6 , 46 . The Altai argali sheep is currently classified as Endangered following International Union of the Conservation of Nature (IUCN) criteria, and populations are highly fragmented across the country 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Our discussions with area residents suggested that during the late twentieth century, big game animals were regularly seen atop Tsengel Khairkhan, but have not been observed there in decades. Big game populations have declined dramatically across Mongolia during the last thirty years, primarily due to illegal poaching driven by international wildlife markets 6 , 46 . The Altai argali sheep is currently classified as Endangered following International Union of the Conservation of Nature (IUCN) criteria, and populations are highly fragmented across the country 47 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in a previous countrywide survey for Ovis darwini by Lkhagvarsuren et al (2016), C. canadensis was not reported to be present in our study area. It is a surprising discovery that C. canadensis has apparently undergone a range expansion as the species has declined by more than 90% in Mongolia over the last decades (Zahler et al 2004). This is especially interesting, as our study area had high presence of humans and livestock, which has previously been found to negatively affect C. canadensis populations (Thapaliya 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This includes a rapidly expanding tourism industry (Mavroidi 2008;Alexander et al 2019;Mijiddorj et al 2019). Large parts of High Asia are remote which results in law enforcement being difficult, increasing the possibility of illegal hunting of wildlife for consumption and trade (Mishra and Fitzherbert 2004;Zahler et al 2004).…”
Section: Local Socio-economic Factorsmentioning
confidence: 99%